Retracted: Interprovincial Relations in Formative Phase of Federal Nepal - Subedi, Girdhari (Journal of Political Science, 2021)
On 17th September 2021 the Editorial Board of the Journal of Political Science agreed to retract the article ‘Interprovincial Relations in Formative Phase of Federal Nepal’ published in Journal of Political Science, Vol.21 pages 9-18 (DOI: https://doi.org/10.3126/jps.v21i0.35259 ) because the article was found to have significant overlap with other published sources. See retraction notice DOI: https://doi.org/10.3126/jps.v21i0.39813